Pengaruh Pelayanan Dengan Prinsip-Prinsip Syariah Terhadap Kepuasan Konsumen Umum Rawat Jalan (Studi Kasus Di Rumah Sakit Universitas Sebelas Maret Surakarta) - Sumadi Sumadi; Tino Feri Efendi; Tutik Agustini; Salsabila Aslama (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine if the quality of services, prices, and facilities affect the satisfaction of general outpatient patients at Sebelas Maret University Hospital. The population in this study was general outpatients of Sebelas Maret University Hospital. This research uses quantitative methods. The population in this study was general outpatients of Sebelas Maret University Hospital. Sampling techniques of this study using simple random sampling techniques and obtained the number of 100. Data Collection Techniques used through questionnaires, interviews, and documentation. Independent variables that will be studied in this study are Service quality (X1), price (X2), and facilities (X3). The dependent variable that will be examined in this study is patient satisfaction (Y). Data Analysis Techniques used through Validity Test, Reliability Test, and Classic Assumption Test. The hypothesis test in this study used Multiple Linear Regression Analysis, t-Test (partial), F Test (simultaneous), and Determination Coefficient (R2). The results showed that 1) the quality of service significantly affected the satisfaction of general outpatient patients at Sebelas Maret University Hospital, 2) the price significantly affected the satisfaction of general outpatient patients at Sebelas Maret University Hospital, 3) the facility significantly affected the satisfaction of general outpatient patients at Sebelas Maret University Hospital, and 4) the quality of services, prices, and facilities jointly significantly affected the satisfaction of general outpatient patients at Sebelas Maret University Hospital.